Fashion illustration : wedding dress inspiration - Jing, Peng (Fashion designer) (Design Media Publishing (UK) Limited, 2018)
"A wedding dress is the dream dress of every woman. This book invites Peng Jing (China Top 10 Fashion Designer) as the writer to introduce the working process of wedding dress, relationship between wedding dress design and illustrations, and how to paint wedding dress illustrations from the perspective of design and painting. It includes knowledge such as painting tools and materials, body structure, texture expression and detail expression, and detailed step-by-step tutorials of illustrations and a large amount of delicate illustration works, including wedding dresses, formal dresses, Chinese wedding dresses and accessories. Through this book, readers can master the basics of wedding dress illustration easily and paint excellent wedding dress illustrations."--